2015
DOI: 10.1056/nejmoa1412278
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone or Pentoxifylline for Alcoholic Hepatitis

Abstract: Pentoxifylline did not improve survival in patients with alcoholic hepatitis. Prednisolone was associated with a reduction in 28-day mortality that did not reach significance and with no improvement in outcomes at 90 days or 1 year. (Funded by the National Institute for Health Research Health Technology Assessment program; STOPAH EudraCT number, 2009-013897-42 , and Current Controlled Trials number, ISRCTN88782125 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
670
8
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(713 citation statements)
references
References 22 publications
16
670
8
19
Order By: Relevance
“…The only difference between the two cohorts was related to the period of enrollment; patients in the first cohort were enrolled during 2013, and those of the validation cohort were enrolled in 2014 and 2015. The response to steroid in our population of SAH was slightly higher with fewer NRs compared to Western countries (35%) 4, 29. The reasons for these differences between countries are unclear but may involve differences in genetic and environmental factors between Indian and Western patients that contribute to differences in the response to corticosteroids.…”
Section: Discussionmentioning
confidence: 64%
“…The only difference between the two cohorts was related to the period of enrollment; patients in the first cohort were enrolled during 2013, and those of the validation cohort were enrolled in 2014 and 2015. The response to steroid in our population of SAH was slightly higher with fewer NRs compared to Western countries (35%) 4, 29. The reasons for these differences between countries are unclear but may involve differences in genetic and environmental factors between Indian and Western patients that contribute to differences in the response to corticosteroids.…”
Section: Discussionmentioning
confidence: 64%
“…The STOPAH investigators found that while prednisolone was associated with a non-significant reduction in mortality, neither steroid (14% treatment vs. 18% non-treatment, P = 0.06) nor pentoxifylline (16% treatment vs. 16% non-treatment, P = 0.69) were effective in reducing 28-day mortality. 13 Long-term survival was unaffected by treatment as no differences in mortality between treatment groups were noted at 90-day or 1-year follow-up. 13 While not without its limitations, such as lack of liver biopsy diagnosis confirmation and appreciably lower mortality rates than previous trials, STOPAH is the largest, most comprehensive piece of AH literature currently available.…”
Section: Discussionmentioning
confidence: 90%
“…In its severe form, AH can result in 20-50 % mortality at 3 months. The only available therapies that improve survival are corticosteroids and liver transplantation [5,6]. The efficacy of pentoxifylline is debatable, based on recent large clinical trials [6].…”
mentioning
confidence: 99%
“…The only available therapies that improve survival are corticosteroids and liver transplantation [5,6]. The efficacy of pentoxifylline is debatable, based on recent large clinical trials [6]. The efficacy of prednisolone has been shown in meta-analyses of individual data and was partially confirmed in the recent STOPAH trial [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation